Long-Term Donor Chimerism Monitoring for Relapse Risk Assessment After Pediatric Allo-HSCT - Prażmo A; Skowera P; Zaucha-Prazmo A; Lejman M (The Application of Clinical Genetics, 2025)
Anna Prażmo,1 Paulina Skowera,2 Agnieszka Zaucha-Prazmo,3,* Monika Lejman2,* 1Student Scientific Society of Independent Laboratory of Genetic Diagnostics, Medical University of Lublin, Lublin, Poland; 2Independent Laboratory of Genetic Diagnostics, Medical University of Lublin, Lublin, Poland; 3Department of Paediatric Haematology, Oncology and Transplantology, Medical University of Lublin, Lublin, Poland*These authors contributed equally to this workCorrespondence: Monika Lejman, Email monika.lejman@umlub.plObjective: Allo-HSCT is a well-established treatment for several hematological malignancies. Relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains a significant problem and is associated with a poor prognosis and low overall survival. Chimerism analysis is one of the tools applied in post-transplant monitoring, as an increasing fraction of recipient cells after HSCT has been linked to a higher risk of relapse.Study Design: In this retrospective, single-centre study we have analysed the data of patients treated with allo-HSCT for a range of hematological malignancies in the Department of Paediatric Haematology, Oncology and Transplantology, Medical University of Lublin, Poland, between years 2002– 2018.Results: For all 103 patients 3-years OS was 72.6 (95% CI: 64.3– 82.0) and 3-years EFS was 72.0 (95% CI: 63.5– 81.6). There were no differences in 3-years OS and EFS in group of patients who achieved FDC < 14 and > 14 days: 67.9 (95% CI: 57.4– 80.3) vs 81.9 (95% CI: 69.7– 96.2), p = 0.220 and 66.0 (95% CI: 55.3– 78.7) vs 84.1 (95% CI: 72.3– 97.9), p = 0.073, respectively. Early FDC achievement was not significantly associated with risk of relapse, p = 0.181. Based on multivariate Cox regression analysis AML/MDS increased risk of relapse 3x compared to ALL, HR = 2.72, CI95 [1.24– 5.98], p = 0.013; PB/CB increased the risk nearly 3x compared to cells from BM, HR = 2.52, CI95 [1.12– 5.65], p = 0.025.Conclusion: In presented study, achieving early FDC was not associated with lower risk of relapse and had no impact on overall and event-free survival. However, the study presents a unique data of very early chimerism in a large cohort of paediatric patients with haematological malignancies treated within a single unit. Possible extensions to this study, to include analysing more data from a larger patient cohort, may allow us to determine the exact prognostic value of very early chimerism analysis to establish relevant cutoff values and risk thresholds for intervention.Keywords: hematopoietic chimerism, allo-HSCT, children, relapse